The potential of Google Classroom web service for lecturers of higher educational establishments under pandemic conditions - Leila Yu. Sultanova; Oksana P. Tsiuniak; Liudmyla O. Milto; Maryna O. Zheludenko; Lyudmyla M. Lyktei; Larisa M. Petrenko; Aleksandr D. Uchitel (Academy of Cognitive and Natural Sciences, 2021)
Researches and publications on using Google Classroom web service for lecturers of higher educational establishments under pandemic conditions are analysed. The current state of higher education under pandemic conditions is characterised. Features of Google Classroom web service have been identified. The methodical development for lecturers of higher educational establishments "Potential of using Google Classroom web service" is described. Criteria and levels of using Google Classroom web service are defined. Initial diagnostic of the levels of using Google Classroom web service was conducted. During the diagnostic was revealed that most respondents have insufficient levels of theoretical knowledge and practical skills. In order to increase the level of using Google Classroom web service, the methodological development was implemented. As a result, positive dynamics in the levels of theoretical knowledge and practical skills of using Google Classroom web service was revealed. The effectiveness of the obtained results was confirmed by Fisher's criterion.